2017
DOI: 10.1186/s12889-017-4035-z
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities in establishing a collaborative multisite observational study of chronic diseases and lifestyle factors among adults in Puerto Rico

Abstract: BackgroundPrevalence of chronic diseases and unhealthy lifestyle behaviors among the adult population of Puerto Rico (PR) is high; however, few epidemiological studies have been conducted to address these. We aimed to document the methods and operation of establishing a multisite cross-sectional study of chronic diseases and risk factors in PR, in partnership with academic, community, clinical, and research institutions.MethodsThe Puerto Rico Assessment of Diet, Lifestyle and Diseases (PRADLAD) documented life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…The convenience sampling in primary clinics from the San Juan metropolitan area reduces the generalizability of our results, and it is possible that those seeking primary care services were either more health-conscious or needed clinical care due to pre-existing conditions. However, health insurance coverage in Puerto Rico is high, thus most people had access to care in the recruitment clinics, and their diverse locations improved the sociodemographic representation of our sample [ 12 ]. The prevalence of chronic conditions reported in our study were similar to those reported by BRFSS and previous studies, suggesting that we captured accurate occurrence of disease among adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The convenience sampling in primary clinics from the San Juan metropolitan area reduces the generalizability of our results, and it is possible that those seeking primary care services were either more health-conscious or needed clinical care due to pre-existing conditions. However, health insurance coverage in Puerto Rico is high, thus most people had access to care in the recruitment clinics, and their diverse locations improved the sociodemographic representation of our sample [ 12 ]. The prevalence of chronic conditions reported in our study were similar to those reported by BRFSS and previous studies, suggesting that we captured accurate occurrence of disease among adults.…”
Section: Discussionmentioning
confidence: 99%
“…The Puerto Rico Assessment of Diet, Lifestyle, and Diseases (PRADLAD) study is a cross-sectional survey of a convenience sample of 380 adults living in Puerto Rico, conducted in 2015 with the goal of assessing lifestyle risk factors and health conditions among adults in the island. Study design and methodology have been described in detail previously [ 12 ]. Participants were patients waiting for a medical appointment, or visitors, recruited from three primary care clinics (a community clinic ( n = 206); a research-based clinic ( n = 101); and a city hospital clinic ( n = 73), selected for their strategic locations, facilities, and wide patient representation) in the San Juan metropolitan area.…”
Section: Methodsmentioning
confidence: 99%
“…Data were analyzed from the cross-sectional survey Puerto Rico Assessment of Diet, Lifestyle, and Diseases (PRADLAD). Details of the study recruitment and procedures have been previously described [19]. Briefly, between July and November 2015, a convenience sample of adults living in the San Juan, PR metropolitan area was recruited by advertising at three partner clinics: a research center and medical care facility, a primary care clinic within a city hospital, and a nonprofit federally-funded primary community health care center.…”
Section: Methodsmentioning
confidence: 99%
“…The Hispanic Community Health Study gave specific guidance towards focusing on preventive risk factors that are culturally tailored to specific Hispanic groups (Daviglus, Pirzada, & Talavera, 2014), a call echoed by other researchers studying Puerto Ricans (Mattei et al, 2017). By researching and gaining knowledge about Puerto Rican environment, diet and gut microbiome, we build a greater understanding of the comprehensive exposures and intermediaries that compromise Puerto Rican health.…”
Section: Discussionmentioning
confidence: 99%
“…Ricans (Mattei et al, 2017;. This minority group is disadvantaged in terms of their socioeconomic status, and several lifestyle exposures (Lucas, Freeman, & Adams, 2016;Martell, Garrett, & Caraballo, 2016), that contributes to but does not adequately explain their many health disparities when compared to whites and other Hispanic groups (Beckett et al 1996).…”
Section: Discussionmentioning
confidence: 99%